The Geospatial Distribution of Myositis and Its Phenotypes in the United States and Associations With Roadways: Findings From a National Myositis Patient Registry - Hossain, Md M.; Wilkerson, Jesse; McGrath, John A.; Farhadi, Payam N.; Brokamp, Cole; Khan, Md T. F.; Goldberg, Bob; Brunner, Hermine I.; Macaluso, Maurizio; Miller, Frederick W.; Rider, Lisa G. (Frontiers in Medicine, 2022)
Background. Little is known about the spatial distribution of idiopathic inflammatory myopathies (IIM) in the United States (U.S.), or their geospatial associations. Methods. We studied a national myositis patient registry, with cases diagnosed in the contiguous U.S. from 1985-2011 and comprised of dermatomyositis (DM, n=484), polymyositis (PM, n=358), and inclusion body myositis (IBM, n=318) patients. To assess the association of myositis prevalence with distance from roads, we employed log-Gaussian Cox process models, offset with population density. Results. The U.S. IIM case distribution demonstrated a higher concentration in ‘Northeast’. DM, IBM, and cases with lung disease were more common in the East, whereas PM cases were more common in the Southeast. One area in the West and one area in the South had a significant excess in cases of DM relative to PM and of cases with lung disease relative to those without lung disease, respectively. IIM cases tended to cluster, with between-points interactions more intense in the Northeast and less in the South. There was a trend of a higher prevalence of IIM and its major phenotypes among people living within 50 meters of a roadway relative to living beyond 200 meters. Demographic characteristics, rural-urban commuting area, and female percentage were significantly associated with the prevalence of IIM and with major phenotypes. Conclusions. Using a large U.S. database to evaluate the spatial distribution of IIM and its phenotypes, this study suggests clustering in some regions of the U.S. and a possible association of proximity to roadways.